If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23 = 6x + 2 Reorder the terms: -23 = 2 + 6x Solving -23 = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -23 + -6x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 -23 + -6x = 2 + 0 -23 + -6x = 2 Add '23' to each side of the equation. -23 + 23 + -6x = 2 + 23 Combine like terms: -23 + 23 = 0 0 + -6x = 2 + 23 -6x = 2 + 23 Combine like terms: 2 + 23 = 25 -6x = 25 Divide each side by '-6'. x = -4.166666667 Simplifying x = -4.166666667
| 16x^2-72x+75=0 | | 9x+6=-36 | | 32=-6x+2 | | 69-1=9+20 | | 17x+20=16x+20 | | 10x+1=9x+12 | | -23=6*4+2 | | x+77+x+62=45 | | 32=-6*-5+2 | | 58=-6*-7+2 | | 2x-5=4.4 | | 68=-6*-10+2 | | 4x-10-3x-(x-7)= | | 4(8b-5)=-4b+16 | | 7x-4+30=5+10x | | 7x-6+3x-9+5x=180 | | 56+x+85=42 | | X+15=8.4 | | x/2+1/4=3/4 | | x-(3x-5)+(6x+14)=180 | | 2y+5x=13 | | 8(4n+7)=-34+2n | | 3x+6x=981 | | 2x+44=12x | | -27+8n=5(2n-3) | | x^2+4x-4=-9 | | 9x-2+48=11x+22 | | -8(-4-5a)=32-5a | | x-y-2z=2 | | 110-2x=180 | | -2(7k+4)=-40-6k | | abc+4b=9d |